Implementing the International Health Regulations (2005) in the World Health Organization Western Pacific Region - Li, Ailan (Western Pacific Surveillance and Response, 2013)
It has been 10 years since severe acute respiratory syndrome (SARS) – the first emerging infectious disease of global significance in the 21st century – occurred in the Western Pacific Region in 2003. At that time, the revision process of the International Health Regulations (IHR) was underway. However, as considered by MacKenzie and Merianos in this issue of WPSAR “perhaps the most important legacy from SARS was the additional urgency and focus given to the revision of IHR by the World Health Assembly.”2 Recently, IHR (2005) has been used as a global tool to collectively respond to the emergence of Middle East Respiratory Syndrome coronavirus (MERS-CoV) from 2012 and the avian influenza A(H7N9) virus in 2013.